Pembuatan Bahan Konduktor Kabel Listrik dari Deposit dan Scrap Tembaga - Mohamad Marhaendra Ali; Arif Indro Sultoni (Jurnal Teknologi Bahan dan Barang Teknik, 2019)
The conductivity of electrical cables is determined by the value of the current conductivity of the conductor material. On the other hand, the conductivity of conductors is strongly influenced by the type of material, cross-section area, and the resistance of conductor material. In this research, conductor material for electrical cables was made by utilizing copper deposit from PCB waste and scrap from the waste of the machining. Research carried out included the melting of copper deposit and scrap into ingots for further testing of the chemical composition and value of the resistance. The test results were compared with the Cu content and resistance of commercial cables on the market. The test results showed that the conductor material from copper deposit and scrap had a copper content (Cu) of about 92% and a resistance value of 0.4 - 0.6 mΩ. This value had a better quality compared to that of electrical cable conductors circulating in the market with copper content (Cu) between 86% - 97% and a resistance value in the range of 8-11 mΩ.Kemampuan hantar kabel listrik ditentukan oleh nilai KHA (Kemampuan Hantar Arus) yang dimiliki oleh material konduktor. Di sisi lain, daya hantar konduktor sangat dipengaruhi oleh jenis bahan, luas penampang, serta  nilai tahanan yang dimiliki oleh bahan konduktor. Pada penelitian ini akan dilakukan pembuatan bahan konduktor untuk kabel listrik dengan memanfaatkan  deposit tembaga dari limbah PCB dan scrap dari sisa machining. Penelitian yang dilakukan meliputi peleburan deposit dan scrap tembaga menjadi ingot untuk selanjutnya dilakukan pengujian komposisi kimia dan nilai tahanannya. Hasil uji yang diperoleh dibandingkan terhadap nilai kadar Cu dan hambatan dari kabel komersial yang beredar di pasaran. Hasil pengujian  menunjukkan bahwa bahan konduktor dari deposit dan scrap tembaga mempunyai kandungan tembaga (Cu) sekitar 92% dan nilai tahanan 0,4-0,6 mΩ. Nilai tersebut memiliki kualitas yang lebih baik apabila dibandingkan  dengan konduktor kabel listrik yang beredar di pasaran dengan kandungan tembaga (Cu) antara 86%-97% dan nilai tahanan 8-11 mΩ.